Analisis Faktor-faktor yang Memengaruhi Defisit Anggaran di Indonesia Tahun 2002-2022 - Wanda Natalia Kusumasari; Daryono Soebagiyo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The budget deficit is a state in which the income of the state is lower compared to its expenditures, in other words the state's own income is not enough to meet the government's expenditures. This study intends to look at the influence of the rate of Exchange Rate, Investment, and Inflation on the Budget Deficit in Indonesia in 2002-2022. This study uses a quantitative approach with a descriptive type of research. The method applied in this study is in the form of linear regression with the Ordinary Least Square (OLS) model. The sample data used came from the Central Statistical Agency (BPS), Bank Indonesia (BI), and the World Bank, which is a time series data from 2002-2022. The findings of the study reveal that the Exchange Rate has an important impact on the Budget Deficit. In contrast, Investment and Inflation do not have a notable impact on the Budget Deficit.